PROFIL HEMOGLOBIN, LINGKAR LENGAN ATAS, DAN PENGETAHUAN IBU HAMIL SEBAGAI INDIKATOR ANEMIA: STUDI DESKRIPTIF DI PUSKESMAS NARAS - Ahifa Taurisia; Jelmila, Sri Nani; Arief Rinaldy (Nusantara Hasana Journal, 2025)
Anemia during pregnancy remains a significant public health problem with serious consequences for both mother and fetus. Nutritional status, level of knowledge, and adherence to iron supplementation are known to be associated with the incidence of anemia. This study aimed to evaluate hemoglobin levels, mid-upper arm circumference (MUAC), and maternal knowledge as indicators of anemia in pregnant women at the Naras Primary Health Center. This descriptive study employed a cross-sectional approach involving 71 pregnant women selected through consecutive sampling. Data collection included hemoglobin measurement using a hematology analyzer, MUAC measurement with a standard anthropometric tape, and structured interviews to assess knowledge level and adherence to iron tablet supplementation. The findings revealed that 52.1% of the respondents were anemic (Hb <11 g/dL), 36.6% had poor nutritional status (MUAC <23.5 cm), and 40.8% had low knowledge about anemia. Additionally, 36.6% of the respondents were non-adherent to iron tablet consumption. Anemia in pregnant women at the Naras Health Center is multifactorial and closely related to nutritional status, knowledge, and adherence to supplementation. Integrated interventions through nutrition education, regular monitoring of nutritional status, and continuous support from health workers are essential to reduce the prevalence of anemia during pregnancy.